2002
DOI: 10.1106/108201302026117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Deficiency on Melon (Cucumis melo L.) Texture and Glassiness Incidence During Ripening

Abstract: The effects of calcium deficiency on the appearance of ''glassiness'' or ''watercore'' and texture evolution in cantaloupe muskmelon (Cucumis melo L.) and on polygalacturonase (PG) and b-galactosidase activities and their relation to ethylene production were studied. Watercore increased in melons cultivated with calcium-deficient nutrient solutions, as did ripening, which could be related to their lower calcium content. Whole fruit firmness and flesh firmness decreased from 34 days after set (DAS) in control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…Aside from high content, Ca nutrients play an important role in the growth and fruit quality of melons. Calcium deficiency causes rapid fermentation of the fruit under forced culture conditions, an incidence of glassiness and reduces fruit hardness (Serrano et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from high content, Ca nutrients play an important role in the growth and fruit quality of melons. Calcium deficiency causes rapid fermentation of the fruit under forced culture conditions, an incidence of glassiness and reduces fruit hardness (Serrano et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from high content, Ca nutrients play an important role in the growth and fruit quality of melons. Calcium deficiency causes rapid fermentation of the fruit under forced culture conditions, an incidence of glassiness and reduces fruit hardness (Serrano et al 2002). In addition, Ca deficiency reduces root development in melon (Fujimoto 2000), indicating that Ca possibly facilitates good rearing of seedlings through root development.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic use of California melons in ''fresh cut'' processing is increasing, and fruit firmness is also critical for that use. Premature softening and ''glassiness'' of melons (a physiological disorder in which fruit flesh appears water-soaked) have been associated with low calcium concentration in the fruit tissue (Lester andGrusak, 1999, 2001;Madrid et al, 2004;Serrano et al, 2002). Calcium (Ca) is thought to play an integral role in stabilizing cell membranes and slowing tissue degradation (Saure, 2005).…”
mentioning
confidence: 99%
“…Lester and Grusak (2004) reported that multiple foliar Ca applications increased fruit tissue Ca, improving flesh firmness and storage life of honeydew, but not muskmelon. Only in studies conducted in soilless culture has manipulation of nutrient solution Ca concentration yielded significant muskmelon fruit quality effects (Bernadac et al, 1996;Madrid et al, 2004;Serrano et al, 2002). Despite these generally disappointing results, California growers commonly apply soluble Ca fertilizers such as calcium nitrate, calcium thiosulfate, and calcium chloride to melons during fruit development; application through drip irrigation is particularly popular.…”
mentioning
confidence: 99%
“…excessive irrigation in periods with high insolation, shading, or unbalanced fertilization (Cornillon et al, 2000;Madrid et al, 1997Madrid et al, , 2001Nishizawa et al, 1998Nishizawa et al, , 2004a. The disorder symptoms include a glassy texture of the flesh and water exudation (a watercore disorder), accompanied by flavor degradation with a tendency to alcoholic fermentation, normal levels of flesh sugars, excessive softening, and increased polygalacturonase activity, intercellular spaces, and membrane permeability (du Chatenet et al, 2000;Madrid et al, 1997;Nishizawa et al, 2004b;Serrano et al, 2002). The watersoaking disorder is characterized by lower calcium concentration in the NaCl-soluble fraction of the mesocarp tissue of the ripe fruit from the basal hemisphere but not in tissue from the inner mesocarp of the distal hemisphere (Nishizawa et al, 2004a).…”
mentioning
confidence: 99%